Deep Learning Acoustic Model in Microsoft Cortana Voice Assistant - Li, Jinyu (Microsoft, 2017)
Deep Learning Acoustic Modeling has been widely deployed to real-world speech recognition products and services that benefit millions of users. In this talk, I will first briefly describe selected developments and investigations at Microsoft to make deep learning networks more effective under production environment, with the focus on computational cost reduction, knowledge transfer and model robustness. Then, I will introduce our recent efforts in adapting models with unlabeled data and the work of separating speeches from multi-speakers.